(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
From the perspective of gender geography, in this article studies the diversity of spatial and social practices of the children and school con- text considering their actions in moments of free play. The study of geo- graphical space is proposed here as dialectical because the situations are studied dialectic within a framework of asymmetries patriarchal own system.